SINDESO: FOSTERING HIGH ORDER THINKING SKILLS THROUGH REAL PRACTICE EDUCATION - Chusna Apriyanti (IJIET (International Journal of Indonesian Education and Teaching), 2021)
This study aims to know the Sindeso program hosted by Sekolah Alam Pacitan and to know the development of Higher Order Thinking Skills (HOTS) in Sindeso program. The researcher used a descriptive qualitative research design. The researcher collected the data from the students joined Sindeso, the teachers, the communities. There were 130 students divided into ten groups. The research was conducted in February 2018 during the Sindeso program in Wonoanti, Tulakan Pacitan, and Sekolah Alam Pacitan. The data were collected by implementing observations and interviews. After being collected, the data were analyzed using Miles and Huberman data analysis step, including data condensation, data display, and drawing conclusion/verification. The result showed that the Sindeso program is conducted into three stages: preparation, main, and evaluation. Higher-order thinking skills (HOTS) is developed through analyzing, evaluating, and creating process.